The Influence of Attitude Toward Money, Locus of Control, Financial Self-Efficacy and Self-Control on Financial Management Behavior - Welly Chandra; Ary Satria Pamungkas (Graduate Program of Universitas Tarumanagara, 2023)
The aim of this study was to determine the role of Attitude toward Money, Locus of Control, Financial Self-Efficacy and Self-Control in explaining Financial Management Behavior among workers that use E-commerce and live in Jakarta. The samples used in this study are workers that use E-commerce and live in Jakarta. This study collected 208 samples who are workers that use E-commerce and live in Jakarta. The respondents selected by using convenience sampling method. This research used Partial Least Square-Structural Equation Modeling (PLS-SEM) to analyze data. The result of this study indicated that Attitude toward Money, Locus of Control, Financial Self-Efficacy and Self-Control has positive influence on explaining Financial Management Behavior.